SISTEM INFORMASI ALUMNI (TRACER STUDY) BERBASIS WEB (Studi Kasus : Sekolah Tinggi Teknologi Ronggolawe Cepu) - Novita Tiyana Putri; Joko Handoyo (Sekolah Tinggi Teknologi Ronggolawe Cepu, 2017)
High school Technology Ronggolawe (STTR) Cepu was one of the colleges that have the obligation to provide the media withinformation about alumni in order for the establishment of good communication between fellow alumni. Therefore the authors do a researchby designing information systems alumni, such as courses, year of graduation, the place of work as well as other information related toalumni.The purpose of this research is able to collect and maintain accurate data and serves from alumni. The design of informationsystems is modeled into the diagrams in the UML (Unified Modeling Language). Programming using PHP-based Framework. FrameworkCodeIgniter developed to facilitate in developing application structure file source code using the approach the concept of MVC (Model ViewController). System development method of SDLC (System Development Life Cycle) in the model of the waterfall. The research of usingtesting functionality testing and black box testing.The results of test functionality of information systems alumni (tracer study) were declared worthy in terms of functionality, with100% results on black box testing. This research is expected to help high schools Technology Ronggolawe (STTR) Cepu in performing datastorage management and alumni.